Feasibility of family based screening for colorectal neoplasia: experience in one general surgical practice. Issue 1 (January 1993) - Stephenson, B M; Murday, V A; Finan, P J; Quirke, P; Dixon, M F; Bishop, D T
Abstract : Relatives of patients with colorectal cancer have on average a two to threefold increased risk for developing bowel neoplasia although in some families the risk is much higher. This study examined the compliance for endoscopic screening and faecal occult blood testing among first degree relatives of patients with colorectal cancer to determine the feasibility of offering a screening service in a surgical practice. The endoscopic method (flexible sigmoidoscopy or colonoscopy) offered depended upon the extent of family history. Spouses of patients were offered flexible sigmoidoscopy as a group for comparison. Compliance in first degree relatives was significantly higher than in spouses (69% v 47%, p < 0.01) and among those relatives of patients who had died recently from colorectal cancer but time since diagnosis in the index case had no effect. Adenomas were found in 14 of 92 (15%) relatives and three of 30 (10%) spouses. It is estimated that, under our screening guidelines, every 100 patients with colorectal cancer would generate a list of 35-40 relatives who would be screened once by flexible sigmoidoscopy and perhaps 75, who because of their young age, might be screened twice in their lifetime. Also, from this same 100 patients, about 12-15 relatives would merit entry in a colonoscopic screening programme because of their more extensive family history. These results indicate that endoscopic screening of relatives of patients with colorectal cancer is feasible within a practice.